P-Q Controller of Grid-Connected Microgrid with Smart Inverter Based PV Distributed Energy Resources - Behera C.K.; Thakur A.K.; Singh S.P. (My University, 2025)
The real and reactive power control for Inverter interfaced distributed energy resource (DER) based on sliding-mode control (SMC) strategy has been prposed for the grid-integrated microgrid. The proposed control strategy furnishes a very fast and stable control operation on the terminal voltage and frequency of DER units. Additionally, it also maintains the output power quality of the rest of the DER units despite the unbalanced loading with the grid. The reliability of the SMC controller has been compared with the conventional Proportional Integral (PI) controller through time-domain simulation in PSCAD/EMTDC software of grid-connected microgrid under various loading conditions. © 2020 IEEE.